Morphometric and Length–Weight Relationships of Three Penaeid Shrimp Species in the Waters of Jaloh Island, Batam City - Masni Masni; Fauziah Syamsi; Yarsi Efendi (Universitas Labuhanbatu, 2025)
Background: Understanding the relationship between body length and weight in commercially essential shrimp species is crucial for assessing growth patterns and estimating biomass. This study aims to evaluate the relationship between body length and weight in three species of shrimp, namely the whiteleg shrimp (Penaeus merguensis), whiteleg shrimp (Litopenaeus vannamei), and tiger shrimp (Penaeus monodon), as a basis for fisheries management in the waters of Jaloh Island, Batam City. Methodology: The samples were collected randomly from the results, catching fishermen at three stations during a day of data collection. Morphometric measurements were conducted on 180 individual, namely whiteleg shrimp (P. merguensis), White shrimp (L. vannamei), and Tiger shrimp (P. monodon). The length-weight relationship has been analyzed for a long time using simple regression using Excel software. The connection between character morphometrics and total length was analyzed with ANCOVA using SPSS 27 software. Findings: The results showed the determinant coefficient of three species shrimp in this study indicates a very close relationship between the growth of length and weight of shrimp. In the P. monodon species, it is known that approximately 78 % of the weight gain is attributed to the increase in shrimp length, while 22 % is attributed to other factors. Characters that influence the total length of the three species are generally overall, where P. merguensis is more influenced by the tail and weight, L. vannamei by the front, back, and body mass, while P. monodon involves almost all parts of the body. Contribution: This approach helps estimate biomass, identify morphological variations between species, and provides a scientific basis in supporting efforts to manage shrimp resources sustainably